2014
DOI: 10.1155/2014/436123
|View full text |Cite
|
Sign up to set email alerts
|

Nonsteroidal Anti-Inflammatory Drugs and Prostatic Diseases

Abstract: Prostatic diseases are characterized by increased activity of cytokines, growth factors, and cyclooxygenases- (COX-) 1 and 2. Activation of COX-1 and COX-2 results in increased levels of prostaglandins and the induction of angiogenic, antiapoptotic and inflammatory processes. Inhibition of COX enzymes by members of the widely used nonsteroidal anti-inflammatory drug (NSAID) class of drugs decreases prostaglandin production, and exerts a variety of anti-inflammatory, antipyretic, and antinociceptive effects. Wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
1

Year Published

2015
2015
2025
2025

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 66 publications
0
33
1
Order By: Relevance
“…Both COX−1 and COX−2 have been shown to be expressed in BPH tissues [23]. Activation of COX−1 and COX−2 has been known to increase the levels of prostaglandins and induce angiogenic, antiapoptotic and inflammatory processes [24]. In our study, flurbiprofen monotherapy improved baseline IPSS and PVR, but not flow measures.…”
Section: Discussionmentioning
confidence: 45%
“…Both COX−1 and COX−2 have been shown to be expressed in BPH tissues [23]. Activation of COX−1 and COX−2 has been known to increase the levels of prostaglandins and induce angiogenic, antiapoptotic and inflammatory processes [24]. In our study, flurbiprofen monotherapy improved baseline IPSS and PVR, but not flow measures.…”
Section: Discussionmentioning
confidence: 45%
“…NSAIDs act by inhibiting cyclo-oxygenase 1 (COX-1) and cyclo-oxygenase 2 (COX-2) enzymes, which catalyse the production of eicosanoids. Eicosanoids include prostaglandins, thromboxanes, leukotrienes and lipoxins, which all generally mediate inflammation 70. The inhibition of these products makes NSAIDs a potent anti-inflammatory, antipyretic and analgesic drug 70…”
Section: Non-steroidal Anti-inflammatory Drugsmentioning
confidence: 99%
“…In particular, C-reactive protein as a systemic inflammation marker was reported to be a poor prognostic factor in several types of cancers [6,7]. Others and we have also revealed that neutrophil-to-lymphocyte ratio (NLR) is an independent prognostic factor in various solid malignancies, including renal cell carcinoma, bladder urothelial carcinoma, and prostatic carcinoma [8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 80%